Decisive role of electron-phonon coupling for phonon and electron instabilities in transition metal dichalcogenides - Zishen Wang; Chuan Chen; Jinchao Mo; Jun Zhou; Kian Ping Loh; Yuan Ping Feng (Physical Review Research, 2023)
The origin of the charge density wave (CDW) in transition metal dichalcogenides has been hotly debated, and no conclusive agreement has been reached. Here, we propose an ab initio framework for an accurate description of both Fermi surface nesting and electron-phonon coupling (EPC) and systematically investigate their roles in the formation of the CDW. Using monolayer 1H-NbSe_{2} and 1T-VTe_{2} as representative examples, we show that it is the momentum-dependent EPC that softens the phonon frequencies, which become imaginary (phonon instabilities) at CDW vectors (indicating CDW formation). In addition, the distribution of the CDW gap opening (electron instabilities) can be correctly predicted only if EPC is included in the mean-field model. These results emphasize the decisive role of EPC in the CDW formation. Our analytical process is general and can be applied to other CDW systems.